2009
DOI: 10.2113/jeeg14.4.163
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Mode Decomposition Operator for Dewowing GPR Data

Abstract: Signal processing tools available to ground penetrating radar data used for shallow subsurface imaging and hydrogeophysical parameter estimation are significantly handled using the same tools available to seismic reflection data. Overall, the same tools produce interpretable images from both data types, but particular noise (wow noise) in electromagnetic data must be removed before stable and accurate quantitative results can be produced. Wow noise is an inherent, nonlinear electromagnetic interference and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…For each trace, it calculated the mean of the points on either side of that point within a specified time range. Then, the mean was subtracted from the original point (Bradley et al, 2009). The gain function step helped to visualize data late in the time series of each trace.…”
Section: Methodsmentioning
confidence: 99%
“…For each trace, it calculated the mean of the points on either side of that point within a specified time range. Then, the mean was subtracted from the original point (Bradley et al, 2009). The gain function step helped to visualize data late in the time series of each trace.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, attention must be paid to avoid potential distortion effects on the signal and, hence, loss of information [57]. According to the literature, time-varying high-pass filtering or the Empirical Decomposition Method (EMD) [58] are regarded as alternative processing methods to de-wow. Figure 6 shows the reference GPR radargram after applying a de-wow filter.…”
Section: Lower Frequency Harmonics Removalmentioning
confidence: 99%
“…Noise due to the surrounding media and the inherent loss of the GPR signal usually lowers the SNR in a GPR section, especially at relatively late recording times [58,64]. These noise components are generally located outside the main working frequency bandwidth of a GPR system.…”
Section: Band-pass Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a quite large use of this technique in several fields of digital signal processing (Pai et al, 2007;Schmitt et al, 2007;Sweeney-Reed and Nasuto, 2007) only a few examples have been shown in geophysical data processing Battista et al, 2007Battista et al, , 2009Magrin-chagnolleau and Baraniuk, 1999).…”
Section: Introductionmentioning
confidence: 99%